Application of 68Ga‐ and 177Lu‐Labeled FAP Inhibitor in Evaluation and Treatment of Cardiac Fibrosis After Myocardial Infarction - Yiheng Zhao; Xiangyu Su; Boyang Xiang; Shuchen Zhang; Xiang Zhou (MedComm)
ABSTRACT 68Ga and 177Lu‐labeled fibroblast activation protein inhibitor (FAPI) have been introduced for the diagnosis and treatment of multiple malignant and non‐malignant diseases. While several studies have examined the application of 68Ga‐FAPI in myocardial infarction (MI), research on the use of 177Lu‐FAPI for the treatment of MI is still scarce. In this study, we evaluated the effects of 68Ga‐FAPI and 177Lu‐FAPI in cardiac fibrosis after MI using permanent coronary artery ligation rat models. 68Ga‐FAPI‐04 effectively targeted fibroblasts within the MI area. Rats treated with 177Lu‐FAPI‐04 had a significant increase in left ventricular ejection fraction at 28 days post‐MI, with no obvious kidney or liver toxicity. Magnetic resonance imaging and histological analysis revealed a reduced fibrotic area in the 177Lu‐FAPI group. 177Lu‐FAPI‐04 exerted its therapeutic effect by suppressing activation and inducing apoptosis of fibroblasts. In summary, we demonstrated that 177Lu‐FAPI‐04 could effectively target FAP and eliminate activated fibroblasts after MI, thereby contributing to the development of new strategies for the treatment of MI.